Public engagement by researchers of different disciplines in Singapore : a qualitative comparison of macro- and meso-level concerns - Ho, Shirley S. (2020)
Guided by neo-institutional theory, this study compares how researchers from science, technology, engineering, and math disciplines differ from researchers from the arts, humanities, and social sciences fields in terms of how macro- and meso-level concerns shaped their willingness to conduct public engagement. Focus group discussions conducted among researchers based in Singapore revealed that science, technology, engineering, and math and arts, humanities, and social sciences researchers held different macro-level concerns. Particularly, science, technology, engineering, and math researchers raised more concerns about media misrepresentation, while arts, humanities, and social sciences researchers were more concerned about receiving political repercussions and public backlash. With regard to meso-level considerations, researchers from all disciplines cited similar institutional constraints for public engagement; however they possessed varying public engagement competencies and held differing perceptions of their social duty to engage the public. Hence, researchers of different disciplines desired different kinds of media training. Policy and managerial implications as well as directions for future research were provided.